From Concept to Implementation: Development of a Digital Guidebook for Joint Degree Students’ Departure Preparation at State Polytechnic of Malang - Nadia Hanayeen; Prima Beauty Kartikasari; Alvin Nouval; Hilda Cahyani (Transpublika Publisher, 2026)
One of the international student mobility programs implemented by Malang State Polytechnic is the Joint Degree (JD) program, launched in 2019. In 2021, a digital guidebook was developed to help students prepare for their first international experience. However, in 2025, this guidebook has not been updated, even though the program has undergone significant development. This study aims to incorporate the substantial updates into the digital guidebook to facilitate pre-departure preparation. The research method used is Design and Development Research (DDR), which involves the stages of the in-depth interview process for the preliminary study, analysis, product development, evaluation that covers expert validation, field testing, and a user satisfaction survey of the digital guidebook. Research participants included one program coordinator and 14 students from various study programs currently enrolled in the JD program as users. The research instruments used were in-depth interviews and a user satisfaction survey. Meanwhile, thematic analysis was used to analyze the data. Content was validated by the Vice Director of Planning and Partnership; layout was validated by the head of State Polytechnic of Malang (Polinema) Press. Despite expert validation, the guidebook received an unsatisfactory user satisfaction rating (2.52/5.00), indicating critical gaps in content relevance, institutional support, design, and accessibility that must be addressed before implementation. These findings show the importance of collecting user feedback earlier and throughout the DDR development process. They also provide a framework that other polytechnics and vocational institutions can use to develop student-centered pre-departure resources for international mobility programs.